Personajes populares de la provincia de Loja, como referente para una obra pictórica en el género del retrato - Villalta Moncada, Gabriel Alexander (2017)
This dissertation work is framed within the research lines of the Plastic Arts career of the National University of Loja, within the field of research on the human figure. The theoretical - practical work was conceived as a fundamental objective, that of conceiving a pictorial proposal in the genre of the portrait, from the popular characters (people of the working people) of the province of Loja, for which studies were made through plastic resources, Both physiognomic and physiological, that after a study and analysis of field, photographic records, sketches and lace, was determined as objects of pictorial representation, which ultimately constituted as an artistic proposal. The cantons Loja, Saraguro and Zapotillo were considered, as a field of research, because of their location and cultural differences that exist between them, was used in the first instance the inductive method, which starts from the particular towards the general and at the end of the investigation Resorted to the deductive method, in order to compare the results with significant existing proposals.